Increased maternal exercise of moderate intensity improves pregnancy outcomes of gestational diabetes mellitus patients through maintaining the balance of the gut microbiota - Xu, Mengyan; Ye, Xinru; Cai, Fengcheng; Wu, Yingying (Frontiers in Microbiology, 2025)
BackgroundExercise therapy can reduce insulin resistance during pregnancy and improve glucose tolerance in women with gestational diabetes mellitus (GDM), leading to better pregnancy outcomes. This study aimed to investigate the effects of different exercise levels on GDM from the perspective of gut microbiota.MethodsNinety patients with GDM were enrolled and divided into two groups: the L (n = 50) and the M (n = 40) groups. The L group performed 150 min of aerobic exercise per week, while the M group exercised for 200 min per week. After 8 weeks of intervention, fecal samples from each subject were collected for 16S rRNA gene sequencing.ResultsDifferent exercise levels significantly affected membrane rupture and gestational weight gain in GDM patients (p < 0.05), but these effects were not significantly correlated by logistic regression analysis (p > 0.05). After sequencing, 4,712 OTUs and 3,483 OTUs were identified in the M and L groups, respectively, with 2,643 OTUs overlapping between both groups. Compared to the L group, the α-diversity in the M group was significantly increased (p < 0.05). The dominant phyla were Firmicutes, Actinobacteriota, and Bacteroidota. Compared to the L group, the M group had a significantly higher abundance of Firmicutes and a significantly lower abundance of Actinobacteriota. At the genus level, LEfSe analysis revealed that moderate-intensity exercise increased the levels of Faecalibacterium, Agathobacter, Roseburia, and Osillospira, but decreased the abundance of Bifidobacterium and Coprobacillus.ConclusionThere were significant differences in the composition and structure of the gut microbiota of patients with GDM with different exercise levels.